Effects of governance on entrepreneurship: European Union vs. non-European Union - Rodríguez-Gulías, María Jesús (2018)
The purpose of this paper is to analyse the effect of six governance indicators on the rate of creation of new companies between countries that are members of the European Union (EU) and those that are not. H1 states that the various dimensions of governance help to explain the immediate creation of new businesses in European and non-European countries. H2 states that the various dimensions of governance help to explain the deferred creation of new businesses in European and non-European countries.